Patient delay in colorectal cancer patients: associations with rectal bleeding and thoughts about cancer. - Anette F Pedersen (Public Library of Science (PLoS), 2013)
Rectal bleeding is considered to be an alarm symptom of colorectal cancer. However, the symptom is seldom reported to the general practitioner and it is often assumed that patients assign the rectal bleeding to benign conditions. The aims of this questionnaire study were to examine whether rectal bleeding was associated with longer patient delays in colorectal cancer patients and whether rectal bleeding was associated with cancer worries. All incident colorectal cancer patients during a 1-year period in the County of Aarhus, Denmark, received a questionnaire. 136 colorectal cancer patients returned the questionnaire (response rate: 42%). Patient delay was assessed as the interval from first symptom to help-seeking and was reported by the patient. Patients with rectal bleeding (N = 81) reported longer patient intervals than patients without rectal bleeding when adjusting for confounders including other symptoms such as pain and changes in bowel habits (HR = 0.43; p = 0.004). Thoughts about cancer were not associated with the patient interval (HR = 1.05; p = 0.887), but more patients with rectal bleeding reported to have been wondering if their symptom(s) could be due to cancer than patients without rectal bleeding (chi(2) = 15.29; p<0.001). Conclusively, rectal bleeding was associated with long patient delays in colorectal cancer patients although more patients with rectal bleeding reported to have been wondering if their symptom(s) could be due to cancer than patients without rectal bleeding. This suggests that assignment of symptoms to benign conditions is not the only explanation of long patient delays in this patient group and that barriers for timely help-seeking should be examined.